2010
DOI: 10.1002/jcla.20361
|View full text |Cite
|
Sign up to set email alerts
|

Prolidase activity and oxidative status in patients with thalassemia major

Abstract: Significant increases in prolidase activity in patients with thalassemia major may constitute a key parameter in demonstrating a disorder of the collagen metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…In addition, a significant decrease of TAC has been reported in thalassemia patients compared to controls [42,50]. TAC was also lower in thalassemia patients with DFO chelation therapy compared to those without DFO [50] while Cakmak et al [51] reported no significant differences in TAC between thalassemia and control groups, in spite of increased level of oxidant status and oxidative stress index. These findings imply that oxidant-antioxidant balance was disturbed in β-TM and there is enhanced oxidative stress with decreased antioxidant defense irrespective of bilirubin levels.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a significant decrease of TAC has been reported in thalassemia patients compared to controls [42,50]. TAC was also lower in thalassemia patients with DFO chelation therapy compared to those without DFO [50] while Cakmak et al [51] reported no significant differences in TAC between thalassemia and control groups, in spite of increased level of oxidant status and oxidative stress index. These findings imply that oxidant-antioxidant balance was disturbed in β-TM and there is enhanced oxidative stress with decreased antioxidant defense irrespective of bilirubin levels.…”
Section: Discussionmentioning
confidence: 97%
“…The homogenate was centrifuged at 2,800 × g for 10 min at 4°C (20) . Total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) were measured in supernatant and ocular tissue samples as described previously (21) . Briefly, TAS was measured spectrophotometrically using a commercial kit ( …”
Section: Analysis Of Oxidative Stress Markers In the Aqueous Humor Anmentioning
confidence: 99%
“…In addition to collagen turnover, oxidative status and oxidative stress have also been shown to correlate with prolidase activity levels under certain conditions (Aslan et al. 2007; Cakmak et al. 2009, 2010; Selek et al.…”
Section: Prolidase As a Marker For Diseasementioning
confidence: 99%
“…The coupling of oxidative stress with the lack of antioxidant response could explain why prolidase is elevated in this situation. In thalassaemia major, an autosomal recessive blood disorder characterized by widening of the bone marrow cavities and decreased bone mass, elevated prolidase activity has been documented (Cakmak et al. 2010).…”
Section: Prolidase As a Marker For Diseasementioning
confidence: 99%